Nevus with central autoimmune depigmentation. - Milano, A. (European Journal of Pediatric Dermatology, 2015)
Halo nevus is due to an autoimmune inflammation, so that it is considered as a peculiar form of perinevic vitiligo. The white halo is probably the real marker of the autoimmune inflammation, which can destroy the nevus. The entity of the autoimmune inflammation is much variable both from a clinical and histological point of view, ranging from a high clinical evidence to the complete lack of clinical and histological signs (2). The halo surrounding the nevus, which is usually so regular that it seems traced with a compass, can be sometimes irregular, involving only a portion of the perinevic skin or only a central area of the nevus or finally a central area surrounding a darker or anyway different portion of the nevus (1).